Targeting Interleukin-6: All the Way to Treat Autoimmune and Inflammatory Diseases - Toshio Tanaka, Tadamitsu Kishimoto (International Journal of Biological Sciences, 2012)
Interleukin (IL)-6, a cytokine featuring redundancy and pleiotropic activity, contributes to host defense against acute environmental stress, while dysregulated persistent IL-6 production has been demonstrated to play a pathological role in various autoimmune and chronic inflammatory diseases. Targeting IL-6 is thus a rational approach to the treatment of these diseases. Indeed, clinical trials of tocilizumab, a humanized anti-IL-6 receptor antibody have verified its efficacy and tolerable safety for patients with rheumatoid arthritis, Castleman's disease and systemic juvenile idiopathic arthritis, resulting in approval of this innovative biologic for treatment of these diseases. Moreover, a considerable number of case reports and pilot studies of off-label use of tocilizumab point to the beneficial effects of tocilizumab for a variety of other phenotypically different autoimmune and chronic inflammatory diseases. Elucidation of the source of IL-6 and of mechanisms through which IL-6 production is dysregulated can thus be expected to lead to clarification of the pathogenesis of various diseases.